PENDAMPINGAN KREATIF DALAM MERANCANG BAHAN AJAR MATA PELAJARAN FIQIH TENTANG THAHARAH DI SMP ABDI NEGARA SEDAYULAWAS BRONDONG LAMONGAN - Zunaidah; Maftuhah, Maftuhah; Putra Pratama, Aditya; Azlan Syah, Muhammad; Naufal Nabhan, Muhammad; Misbahuddin, Misbahuddin; Muhlis, Muhlis (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Islamic Jurisprudence (Fiqh) learning at the Junior High School (SMP) level plays a strategic role in shaping students' understanding and practice of Islamic teachings, particularly on the topic of purification as a foundation of worship. However, the teaching materials used are often conventional and lack contextualization, thus not fully attracting students' interest in learning. This community service activity aims to describe the implementation of creative mentoring in designing Islamic Jurisprudence (Fiqh) teaching materials for purification at SMP Abdi Negara Sedayulawas. The implementation method uses a participatory approach through classroom observation, discussion, practice of preparing teaching materials, and reflection with teachers during the mentoring activities. Mentoring is carried out using a theory-to-practice approach to bridge theoretical understanding and application of learning in the classroom. The results of the activity show an increase in teacher competence in developing more varied, contextual, and interactive teaching materials through the use of visualizations, simple learning media, and case studies based on everyday life. In addition, learning becomes more interesting and encourages active student involvement in understanding the concept of purification. Thus, this creative mentoring contributes to improving the quality of Fiqh learning planning and strengthening students' understanding of the importance of cleanliness and purity in everyday life.